PENERAPAN MODEL PROJECT BASED LEARNING DENGAN PENDEKATAN TPACK PADA PEMBELAJARAN IPAS KELAS V DI SEKOLAH DASAR - Anshari, Fathia Puti; Qurrotaini, Lativa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is based on the application of Project Based Learning with Technological Pedagogical Content Knowledge (TPACK) which is less than optimal and requires a more interesting learning process and can improve the quality of learning for fifth grade student in Natural and Social Sciences (IPAS) learning. This research aims to describe the application of the Project Based Learning model with the TPACK approach in IPAS learning in fifth grade elementary schools. This research uses a descriptive qualitative analysis method. The research subject were 2 teachers and 10 fifth grade student. Data collection techniques were carried out through observation, interviews, documentation, and triangulation. The result of the study indicate that the application of the project based learning model with the quality of learning and motivate students in the learning process. Teachers have a good conceptual understanding of PjBL with the TPACK approach and this standard covers all PjBL syntax starting from problem determination, planning, project implementation, to evaluation. This technology integration helps smooth concepts into visuals that are easy to understand and is proven by positive student responses showing interesting, interactive, and meaningful learning. Overall, the implementation of the TPACK-based PjBL model has been proven to be able to create active, collaborative learning that is in accordance with the characteristics of 21st-century students.